Effect of environment on structural steel / Azman Mohd Ali and Mohd Abd Fatah Mohd Ramly - Mohd Ali, Azman; Mohd Ramly, Mohd Abd Fatah (1997)
For the past half a decade, Malaysia had been experiencing a series of incidence of building accidents and failures. The height of these incidences is the Highland Towers tragedy in which more than forty people perished. The tragedy sent shock waves across the nation. This was then followed by a number of incidences where buildings under construction crumbled to the ground. Two or three cases of light rail transit (LRT) floating construction girders, which fell to the ground, were also reported. These incidents made headlines in the mass media and stunned the whole nation. Investigations upon investigations were carried out. Eventually, in most cases, investigations revealed that these failures were attributed to design inferiority, human errors, poor construction, and lack of supervision.